Assessing the economic added value of functional food innovation: a case study of pak choy flour by mahesty MSMEs in Malang, Indonesia - Maulita, Shinta; Arifin, Zainul; Rianti, Titis Surya Maha (University of Islam Malang, 2025)
Mahetsy MSMEs processes pak choy vegetables into functional food products, such as pak choy vegetable flour, to extend shelf life and increase added value. However, the amount of added value generated from the processing is unknown. This study aims to analyze the added value generated from processing pak choy vegetables into pak choy vegetable flour by Mahesty MSMEs. The qualitative and quantitative approach employs a purposive sampling method, specifically using business actors as key informants. Data were obtained through interviews, direct observation, and internal company documentation. The analysis method in this study used the Hayami method. The results of the analysis showed that the added value generated from processing one kilogram of pak choy vegetables for IDR 22,000 into pak choy vegetable flour provided an added value of IDR 45,000, or 46.7 percent, which falls within the high added value category (more than 40 percent). This study demonstrates that processing pak choy vegetables into flour offers high economic value to raw materials and holds promising business prospects for developing functional foods. This study suggests that Mahesty MSMES systematically strengthens the system of recording costs and production administration to improve business efficiency and sustainability. The results of this study can serve as a reference for making strategic decisions, as well as encouraging the innovation of derivative products and the development of partnerships to expand the market for Mahesty MSMEs' products.